Efeitos dos treinamentos funcional e concorrente na imunossenescência, composição corporal e aptidão funcional de idosas - Santos, José Carlos Aragão (2021)
Physical exercise is recommended for elderly people to attenuate aging effects, such as sarcopenia and immunosenescence, and to preserve senile autonomy. However, there is no consensus about the better type of training to attenuate immunosenescence in the elderly. Thus, we evaluated the effects of functional (FT) and concurrent (CT) training on immunosenescence, body composition, and functional fitness in elderly women. This randomized controlled trial lasted 16 weeks and consisted of three groups: FT (n = 32), CT (n = 31) and control group (CG, n = 32). Immunosenescence analysis consisted of the evaluation of CD28 and CD57 markers on CD4+ and CD8+ T lymphocytes. Body composition analysis was based on fat mass and lean mass. Functional fitness was analyzed using the to dress and take off the shirt, timed up and go, five times sit-to-stand, 10 m walk, countermovement jump, and gallon-jug shelf-transfer tests that estimated mobility, agility, dynamic balance, strength, and power in activities similar to daily life. Effects over time and between groups were verified, adopting p < 0.05. In immunosenescence, there were effects over time, without group differences, with a reduction in CD4+ T cells in the FT (-10.03%, p = 0.011) and CT (-7.09%, p = 0.015) and an increase in CD8+ T lymphocytes (FT = +42.24%, p = 0.001; CT = +31.49%, p = 0.003). Furthermore, FT and CT maintained naive CD8+CD28+ T cell levels (p > 0.05), while there was a reduction in this subpopulation in the CG (-3.92%, p = 0.040). Also, FT promoted an increase in the memory CD8+CD28-CD57- T lymphocyte subpopulation (+33.05%, p = 0.001). In body composition, effects were detected over time without inter-group differences, with both trainings promoting, from the eighth week of training, a fat tissue reduction (FT = -2.87%, p = 0.008; HT = -2.56%, p = 0.023) and an lean mass increase (FT = +2.21%, p = 0.001; HT = -1.43%, p = 0.033), maintaining this effect until the end of the intervention (p < 0.001). In the functional fitness tests, there was an interaction effect with the FT and CT showing differences compared to the CG (p = 0.001), and no differences between them, except for five times sit-to-stand test in which the FT was superior to the CT (p = 0.045). FT showed differences to the CG as of the fourth week of training in all functional tests, while CT showed this effect later, except for the 10- meter walk test. Therefore, the FT and the CT preserve the immune function and similarly improve body composition, and in functional fitness, the FT promotes adaptations in less time than the CT when compared to the CG.